Konseling kelompok Menggunakan Teknik Expressive Writing Untuk Menurunkan Burnot Pada Peserta Didik SMP Negeri 2 Bringin, Kabupaten Semarang - Ahsana ‘Amala Erliana; Tri Suyati; Ismah Ismah (Institut Nalanda, 2023)
This research was motivated by the high level of learning saturation in students, this can be seen from the results of observations and interviews conducted at SMP Negeri 2 Bringin Semarang Regency. This type of research is quantitative research with an Effectiveness research design. The population in this study was grade IX students at SMP Negeri 2 Bringin with a total of 123 students, the class given was pre-test, namely IX D, which was then taken by seven students to be tested. The sampling technique in this study is a random sampling technique obtained from a learning saturation questionnaire. The results of this study show that group counseling with expressive writing techniques is effective in reducing learning saturation (burnout) in students, this is evidenced by the results of paired sample t-test with the probability of sig values. (2-tailed) 0.003<0.05. As well as the difference in the average score of the learning saturation questionnaire of 28.003% from the pretest and posttest results. This proves that group counseling with expressive writing techniques can reduce learning saturation (burnout) in students.